Baduanjin Training to Improve Parkinson's Disease Gait and Balance Function - DONG Shuangshuang; YAN Hongjie; DONG Qing; CAI Zenglin (康复学报)
ObjectiveTo study the effects of Baduanjin training on the gait and balance function of patients with Parkinson's disease (PD), and to explore Baduanjin training as an effective exercise intervention for PD patients.MethodsA total of 63 patients with mild to moderate PD who met the inclusion criteria were divided into 32 cases in the control group and 31 cases in the treatment group according to the random number table method. The control group was given to maintain the previous conventional drug treatment plan, and the treatment group received 3 weeks of Baduanjin training on the basis of conventional drug treatment. Gait indicators and balance indicators were used to evaluate, analyze and compare the two groups of patients before the test and 3 weeks after the test.Results1) IDEEA gait indicators: there was no statistically significant difference in gait indicators between the two groups before the test (P>0.05); after 3 weeks, compared with those before the test, the two gait indexes of cycle time and stride duration in the treatment group were improved, and the differences were statistically significant (P<0.05), while the comparison of the gait index of the control group before and after the test, the difference was not statistically significant (P>0.05); the cycle time and stride duration of the treatment group were respectively (1.30±0.32) s and (645.90±156.65) ms, which were better than those of the control group (1.56±0.38) s and (765.05±158.93) ms, and the differences were statistically significant (P<0.05). 2) Balance index: there was no statistically significant difference in the balance index between the two groups before the test (P>0.05); the scores and grades of balance test in the treatment group were improved after 3 weeks of the test compared with those before the test (P<0.05), while there was no significant difference in the balance index of the control group before and after the test (P>0.05); the balance test level of the treatment group was 1.00 (1.00, 2.20), which was better than the control group's 2.15 (1.00, 3.83), the difference was statistically significant (P<0.05).ConclusionBaduanjin training can significantly improve the gait and balance ability of patients with mild to moderate PD.